ANALYSIS OF CHALLENGES AND OPPORTUNITIES OF SOCIOLOGY OF DIGITAL SOCIETY IN THE CONTEMPORARY ERA - Badruddin Nasir; Lisbet Situmorang; Diana (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyze the challenges and opportunities of sociology in the digital society in the contemporary era. Digital society, characterized by advances in information and communication technology, faces various significant challenges including digital inequality, privacy and data security issues, and disruption of social values. Inequality in access to technology deepens social and economic disparities, while privacy and data security issues raise concerns about the misuse of personal information. Disinformation and polarization exacerbated by social media also complicate social and political dynamics. However, digital society also offers great opportunities, such as increased access to information that empowers individuals and groups, and the formation of virtual communities that support solidarity and social innovation. Digital technology facilitates more inclusive political participation and enables new economic and educational models that are more flexible and equitable. This study concludes that despite the complex challenges, the wise use of digital technology can support the formation of a more just, inclusive, and participatory society. Therefore, it is important for stakeholders to manage and optimize digital technology in order to achieve a balance between mitigating risks and utilizing existing potential.